Gamification strategies as formative assessment methods. A systematic review - Larrosa, Manuel; Wives, Leandro; Rodés, Virginia (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na Educação, 2023)
This article aims to deepen the analysis of gamification strategies as an appropriate method to offer feedback in the form of formative assessment for elementary school students (K-12). Although gamification strategies have been crucial in the last decade, studies do not discriminate between game elements, such as leaderboards, levels, rankings, etc. For this reason, this study focuses specifically on one of them: awarding badges to learn more about effects. Beyond its potential, incorporating these practices also supposes a significant challenge: the need for evaluation that formal education systems demand. Based on these topics, a systematic review of the literature covering the period of 2011 to 2020 is proposed, specifically delving into the link between gamification strategies in formal education environments and the implementation of formative assessment techniques through gamification by badges.